Structure and Dynamics of Mono- vs. Doubly Lipidated Rab5 in Membranes - Eileen Münzberg (International Journal of Molecular Sciences, 2019)
The Rab5 small GTPase is a regulator of endosomal trafficking and vesicle fusion. It possesses two adjacent cysteine residues for post-translational geranylgeranylation at its C-terminus for the protein to associate with the early endosome membrane. We compare the effect of mono-lipidification of only one cysteine residue with the doubly modified, fully functional Rab protein in both guanosine diphosphate (GDP)- and guanosine triphosphate (GTP)-bound states and in different membranes (one, three, and six-component membranes). Molecular simulations show that the mono-geranylgeranylated protein is less strongly associated with the membranes and diffuses faster than the doubly lipidated protein. The geranylgeranyl anchor membrane insertion depth is smaller and the protein−membrane distance distribution is broad and uncharacteristic for the membrane composition. The mono-geranylgeranylated protein reveals an unspecific association with the membrane and an orientation at the membrane that does not allow a nucleotide-specific recruitment of further effector proteins. This work shows that double-lipidification is critical for Rab5 to perform its physiological function and mono-geranylgeranylation renders it membrane-associated but non-functional.